2022
DOI: 10.1155/2022/8401528
|View full text |Cite
|
Sign up to set email alerts
|

Mycelium-Based Composite: The Future Sustainable Biomaterial

Abstract: Because of the alarming rate of human population growth, technological improvement should be needed to save the environment from pollution. The practice of business as usual on material production is not creating a circular economy. The circular economy refers to an economic model whose objective is to produce goods and services sustainably, by limiting the consumption and waste of resources (raw materials, water, and energy). Fungal-based composites are the recently implemented technology that fulfills the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…Ghazvinian et al [113] found that the MBC of P. ostreatus grown on sawdust (1.02 MPa) had a higher compressive strength than when straw was used (0.07 MPa). Additionally, Chan et al [46] and Alemu et al [18] found that the act of pressing during the production process effectively increased the compressive strength of MBCs.…”
Section: Compression Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghazvinian et al [113] found that the MBC of P. ostreatus grown on sawdust (1.02 MPa) had a higher compressive strength than when straw was used (0.07 MPa). Additionally, Chan et al [46] and Alemu et al [18] found that the act of pressing during the production process effectively increased the compressive strength of MBCs.…”
Section: Compression Strengthmentioning
confidence: 99%
“…Mycelium-based composites (MBCs) are a type of biomaterial that holds great potential for the goal of using agricultural residues in specifically beneficial ways and in the broader embrace of fungal biotechnology [17]. Saprobic fungi can degrade lignocellulosic residues into nutrients through certain bio-fabricated processes wherein their mycelia networks can effectively combine substrate particles together [18]. Ganoderma, Pleurotus, Pycnoporus, and Trametes are the most commonly used fungal genera in the production of MBCs [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Existing research shows that Mycoblock is used in a variety of applications such as packaging materials, insulations, partition walls, utensils, furniture, and different design and architectural [15]. It can significantly reduce the reliance on fossil fuels and the embodied energy required for construction and lower waste left at the end of buildings' life cycles [16].…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate recycling of the wastes produced causes pollution of water bodies, air, landfills, and fertile soils, causing serious damage to the environment. In addition, the rapid and unconscious consumption of natural resources necessitates the search for renewable and recyclable materials and the search for alternative ways to use existing resources (Abdel-Shafy & Mansour, 2018;Alemu et al, 2022;Joshi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%